A Perception-Aware Flatness-Based Model Predictive Controller for Fast Vision-Based Multirotor Flight⁎This research was supported by Drone Delivery Canada, Defence Research and Development Canada, and the Natural Sciences and Engineering Research Council of Canada. Issue 2 (2020) - Greeff, Melissa; Barfoot, Timothy D.; Schoellig, Angela P.
Abstract: Despite the push toward fast, reliable vision-based multirotor flight, most vision-based navigation systems still rely on controllers that are perception-agnostic. Given that these controllers ignore their effect on the system's localisation capabilities, they can produce an action that allows vision-based localisation (and consequently navigation) to fail. In this paper, we present a perception-aware flatness-based model predictive controller (MPC) that accounts for its effect on visual localisation. To achieve perception awareness, we first develop a simple geometric model that uses over 12 km of flight data from two different environments (urban and rural) to associate visual landmarks with a probability of being successfully matched. In order to ensure localisation, we integrate this model as a chance constraint in our MPC such that we are probabilistically guaranteed that the number of successfully matched visual landmarks exceeds a minimum threshold. We show how to simplify the chance constraint to a nonlinear, deterministic constraint on the position of the multirotor. With desired speeds of 10 m/s, we demonstrate in simulation (based on real-world perception data) how our proposed perception-aware MPC is able to achieve faster flight while guaranteeing localisation compared to similar perception-agnostic controllers. We illustrate how our perception-aware MPC adapts the path constraint along the path based on the perception model by accounting for camera orientation, path error and location of the visual landmarks. The result is that repeating the same geometric path but with the camera facing in opposite directions can lead to different optimal paths flown.